2020
DOI: 10.3390/ijerph17155542
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis and Emotion Understanding during the COVID-19 Pandemic in Spain and Its Impact on Digital Ecosystems

Abstract: COVID-19 has changed our lives forever. The world we knew until now has been transformed and nowadays we live in a completely new scenario in a perpetual restructuring transition, in which the way we live, relate, and communicate with others has been altered permanently. Within this context, risk communication is playing a decisive role when informing, transmitting, and channeling the flow of information in society. COVID-19 has posed a real pandemic risk management challenge in terms of impact, preparedness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 38 publications
2
71
0
1
Order By: Relevance
“…Almost all the participants in the study have constantly monitored the content related to the pandemic. In this respect, as De las Heras et al [ 46 ] pointed out, messages about coronavirus have been channelled mainly by the media and especially by generalist television stations. Thus, the main channels used to access the information have been television and the online press, as also concluded in the study by Montaña Blasco et al [ 47 ], followed by WhatsApp and the social network Facebook, which stand out as the most used social networks to learn about the coronavirus [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Almost all the participants in the study have constantly monitored the content related to the pandemic. In this respect, as De las Heras et al [ 46 ] pointed out, messages about coronavirus have been channelled mainly by the media and especially by generalist television stations. Thus, the main channels used to access the information have been television and the online press, as also concluded in the study by Montaña Blasco et al [ 47 ], followed by WhatsApp and the social network Facebook, which stand out as the most used social networks to learn about the coronavirus [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The spread of the pandemic causes uncertainty and fear among the population. Fear and anxiety about a new disease and what could happen can be overwhelming and cause strong emotions in the population [ 40 ]. Being female, having diabetes complications, having changed diabetes behaviors, and feeling isolated and lonely, are associated with being more worried about COVID-19 and diabetes, which is associated with poorer psychosocial health [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the obtained results, it could be concluded that the coronavirus pandemic has a markedly negative impact on the quality of life of diabetics, but the domain of mental quality of life is preserved. Educational plans that improve or include strategies to enhance patient’s quality of life may increase compliance, thereby improving these patients’ diabetes parameters [ 48 ], which is then associated with improved quality of life [ 32 , 33 , 34 ], and a good educational plan includes all these parameters [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studying an individual’s emotions towards the COVID-19 pandemic in social media was discussed in [ 10 , 11 ]. The two studies focused on Spain and used the social media and ecosystem as a source of data to analyze the anger, fear, and sentiment of the public during the pandemic.…”
Section: Related Workmentioning
confidence: 99%